Sympatric competitors have driven the evolution of temporal activity patterns in Cnemaspis geckos in Southeast Asia - Nguyen, Hung Ngoc; Hung, Chih-Ming; Yang, Ming-Yuan; Lin, Si-Min (Scientific reports, 2020)
It is often assumed that animals’ temporal activity patterns are highly conserved throughout evolution. While most geckos are nocturnal, the species in the Cnemaspis genus are mostly diurnal (only a few are nocturnal). This raises a question about the evolution of a diel niche in the Cnemaspis genus. Cnemaspis geckos are distributed across Southeast Asia and are often sympatric with Cyrtodactylus , another widespread gecko genus in the same area. Since both genera are mainly rocky habitat specialists, we hypothesize that Cyrtodactylus may influence the temporal activity pattern of Cnemaspis when they are sympatric through competition. By analyzing habitat data, diel activity, and the existence of sympatric Cyrtodactylus species across the phylogeny of the Cnemaspis genus, we found (1) strong phylogenetic signals in the habitat use trait but not in temporal activity, suggesting that the diel niche of this genus is more labile compared with habitat niche, and (2) a significant association with the temporal activity pattern of Cnemaspis and the sympatry between the two genera, with the former tending to be diurnal when they are sympatric. Originated from a diurnal common ancestor, the release from competition with Cyrtodactylus species might open an opportunity for some Cnemaspis species to shift to nocturnal niches.